Special Convening and Listening Session on Health Equity and Community Outreach and Engagement at National Cancer Institute-Designated Comprehensive Cancer Centers (Mary Ann Liebert, 2021)
In recent years, the cancer research and care community has been more attuned to health equity, increasingly pursuing coordinated and comprehensive action to achieve equitable health outcomes. In addition to its support of a joint research agenda for health disparities in 2017, the National Cancer Institute (NCI) has demonstrated its commitment to addressing health inequities with its 2012 requirement for cancer centers to define and address the needs of a local ?catchment area? and the 2016 mandate for Community Outreach and Engagement (COE). With several years of experience with the COE requirements, there is an opportunity to reflect on the experience to-date and identify opportunities to bolster the impact of COE on equitable cancer outcomes for the future. To do so, the Bristol Myers Squibb Foundation (BMSF) hosted a special convening and listening session in April 2019. The session agenda was cocreated by BMSF and NCI leaders and staff. It brought together 41 individuals, including representatives from the NCI Cancer Centers Program, Division of Cancer Control and Population Health and Center to Reduce Cancer Health Disparities, 22 NCI-designated, emerging or affiliated comprehensive cancer centers, and the broader cancer community. This article captures key themes from that meeting, including an overview of current COE efforts, with a deeper look at how four cancer centers are embedding health equity and COE efforts into their institutions and work, and the successes and challenges they have encountered.